LA MODERNIZACIÓN DE LA GESTIÓN PÚBLICA EN EL PERÚ - Valeriano Ortíz, Luis Fernando (2012)
Modernizing Governance in Peru is one of the most important pillars for the country's sustainable development, requires a political consensus between the branches of government, a legal framework, which includes the central government, regional and Local integrally within a systemic concept that takes into account the experiences included in the achievements and restrictive aspects, regarding the case of laws on public administration reform in the country, which were promulgated and implemented by the various governments in recent decades, and the results were not satisfactory overall. This brief description of the problem, requires further analysis as a basis for projecting a legal device, which by the nature of its content, needs to be widely discussed in the various bodies of state authorities for approval, and must meet the needs of public management of excellence, to help improve the quality of services provided to society and appreciation of public sector workers, for this purpose it is important to review the history of the Public Administration Reform, that have been developed in countries that have been successful and take into account their impact on the development of the regionalization of production and service sectors, in order to know the strengths and weaknesses of the national home front and the opportunities and threats in the environment in this context and propose a reform of the public administration, which takes into account the information technologies and electronic communications.